KOMIK ONLINE SEBAGAI MEDIA PENYULUHAN AGAMA HINDU BAGI GENERASI MILENIAL - I Gede Titah Pratyaksa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Hindu religious counselors in providing Hindu religious education to millennials require a new and unique strategy to deal with the dynamics of the times. Comic media, such as @bogbogbalicartoon and @pinsianart as a means of counseling Hinduism, can turn out to be a tool in socializing Hindu teachings because they are expected to be able to convey information effectively and efficiently. Comics are tools that have the function of conveying a message. As a media, messages conveyed through comics are usually clear, coherent, and fun. For this reason, comic media has the potential to become a source of learning. In this case, learning comics play a role as a tool to convey learning messages. Comics are a form of visual communication media that has the power to convey information in a popular and easy to understand way. This is possible because comics combine the power of images and writing, which are assembled in a storyline making images more easily absorbed. The text makes it more understandable, and the flow makes it easier to follow and remember.Keyword: Online Comics, Media for Extension of Hinduism, Millennial Generation